K. David HARRISON. When languages die: the extinction of the world languages and the erosion of human knowledge. Oxford: Oxford University Press, 2007. 292 pp. ISBN – 978-0-19-537206-9 - Barbosa, Joaquim (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.